Effect of palm oil fuel ash (POFA) as cement replacement material toward concrete microstructure - Rahimah, Yusoff (2012)
Palm Oil Fuel Ash (POFA) is a by-product produced in palm oil mills. These ash having pozzolanic properties that not only enables the replacement of cement but also plays an important role in making strong and durable concrete. For this research, the effectiveness using POFA as cement replacement material towards concrete microstructure was investigated. OPC replaced with 10%, 20 % and 30% of POFA respectively. For compressive strength, concrete cubes 150 x 150 x 150 mm was tested due to 7, 28, and 90 days cured in water. Although strength of POFA concrete did not exceed that of OPC, the compressive strength of POFA concrete is slightly lower than that of OPC at early age but at later ages it is found to be higher than that of OPC concrete. It was found that, the concrete with 20 % of POFA recorded highest compressive strength compare to those POFAmixes. POFA concrete exhibit lower value of porosity compared to OPC concrete. Based on porosity test results, the 20% replacement of the POFA, give the lower of porosity. XRD analysis leads to the fact that the existence of C-S-H increased withcuring age indicating the progress of cement hydration reaction and pozzalanic reaction. From the microstructural analysis (SEM), shows existing of C-S-H gel have lead to a densification structure and increase in strength. Hexagonal platelets of Ca(OH)2 could be observed in some samples.